Stemphylium vesicarium (wallr.) E.G. Simmons: an onion plant pathogen and options for suppression - Takač, Ana; Vuković, Slavica (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
Onion (Allium cepa L.) is one of the most important vegetable species grown worldwide, including the Republic of Serbia. Leaf blight, caused by the fungus Stemphylium vesicarium, is a serious and destructive disease of onion leaves around the world, which limits the quality and quantity of bulbs and seeds. Yield decrease occurs due to a reduced photosynthetic area, which leads to the formation of smaller bulbs of poorer quality. The recommended strategy for control and reduction of SLB inoculum includes crop rotation with other vegetable species or cereals that are not hosts of these fungi, the use of resistant onion genotypes, weed removal, adequate use of nitrogen fertilizers, control of thrips (Thrips spp.), as well as seed treatment, considering that seeds play a significant role in the spread of pathogens. Timely and correct application of foliar fungicides is certainly the key strategy. The timing of application of fungicides with different modes of action is crucial for controlling Stemphylium vesicarium in onion.